2011
DOI: 10.1038/hr.2011.101
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II receptor blocker and long-acting calcium channel blocker combination therapy decreases urinary albumin excretion while maintaining glomerular filtration rate

Abstract: , the NICE-Combi Study GroupMicroalbuminuria is a recognized risk factor and predictor for cardiovascular events in patients with hypertension. We analyzed changes in hypotensive effect, urinary albumin excretion (UAE) and estimated glomerular filtration rate (eGFR) in subjects with hypertension and microalbuminuria as a subanalysis of the results of the Nifedipine and Candesartan Combination (NICE-Combi) Study. A total of 86 subjects with essential hypertension with microalbuminuria (UAE o300 mg g À1 creatini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Treatment with renin-angiotensin aldosterone system (RAAS) inhibitors and calcium channel blockers has a well-known anti-proteinuric effect besides lowering BP. [8][9][10][11] In this study, we aimed to compare the anti-albuminuric effects of an angiotensin II receptor antagonist, valsartan, with a calcium channel blocker, amlodipine, in newly diagnosed hypertensive patients.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with renin-angiotensin aldosterone system (RAAS) inhibitors and calcium channel blockers has a well-known anti-proteinuric effect besides lowering BP. [8][9][10][11] In this study, we aimed to compare the anti-albuminuric effects of an angiotensin II receptor antagonist, valsartan, with a calcium channel blocker, amlodipine, in newly diagnosed hypertensive patients.…”
Section: Introductionmentioning
confidence: 99%
“…21 Our study did not obtain the superiority of combination regimen to increased ARB regimen in reduction of urinary albumin. As one of this reason, it might be considered that urinary albumin level was low; half of patients were categorized into normoalbuminuria in contrast to the NICE-Combi Study.…”
Section: Discussionmentioning
confidence: 48%
“…When nifedipine CR was administered at night, nocturnal BP was significantly decreased [17], and U-Alb excretion may also be decreased. Second, different kinds of CCBs prevent albuminuria to different degrees [11, 12]. In fact, some reports have indicated that nifedipine CR decreased albuminuria.…”
Section: Discussionmentioning
confidence: 99%
“…Nifedipine CR and cilnidipine, but not efonidipine and amlodipine, significantly reduced albuminuria [11]. Combination therapy with standard-dose candesartan and nifedipine CR is more effective than up-titrated candesartan monotherapy for reducing BP and improving U-Alb while maintaining eGFR [12]. Interestingly, nifedipine prevented pressure-induced afferent arteriolar vasoconstriction in an isolated perfused hydronephrotic kidney in rat [25].…”
Section: Discussionmentioning
confidence: 99%